The Effect of Hybrid Telerehabilitation Programme in Individuals with Lumbar Disc Herniation - ÜNLÜ, BEGÜM; TİMURTAŞ, EREN; YILDIZ ÖZER, AYSEL (My University, 2022)
Giriş: Lumbal disk hernisi (LDH) ağrı ve duyusal kayıplara neden olan, kas kuvvetinde kayıplar ve buna bağlı olarak gelişen fonksiyon kaybı ile yaşam kalitesinin azalması ile karakterize muskuloskeletal bir problemdir. Bu çalışmanın amacı LDH tanılı bireylerde hibrit telerehabilitasyon programının etkinliğinin araştırılmasıdır. Gereç-Yöntem: Bu çalışma Ocak-Haziran 2022 tarihleri arasında Marmara Üniversitesi Fizyoterapi ve Rehabilitasyon Bölümü’nde yapıldı. Çalışmaya dahil edilme kriterlerine uyan ve çalışmaya gönüllü olarak katılan 51 LDH tanılı birey alındı. Bireylerin ağrı durumu Vizüel Analog Skala (VAS); kinezyofobi durumu Tampa Kinezyofobi Ölçeği (TKÖ), yaşam kaliteleri SF-12 Yaşam Kalitesi Ölçeği (SF-12); alt ekstremite kuvveti 30 Saniye Otur Kalk Testi (30 STS) ve fonksiyonelliği Zamanlı Kalk Yürü Testi (TUG) ve Oswestry Bel Ağrısı Engellilik Anketi (OBAEA) ile değerlendirildi. Bireyler 8 haftalık hibrit telerehabilitasyon programına dahil edildi. Değerlendirmeler dört defa (D0: program öncesi, D1: 4. haftanın sonu, D2: 8. haftanın sonu, D3: 16. haftanın sonu) yapıldı ve değişimler karşılaştırıldı. Bulgular: Programa alınan 51 hastanın 44’ü kadın 7’si erkekti (yaş ortalaması: 47,13±11,73 yıl). 22 hasta aktif olarak çalışıyordu. 25 hasta daha önce LDH nedeni ile fizik tedavi ve rehabilitasyon programına katılmıştı ve 16 hasta düzenli olarak fiziksel aktivite yaptığını bildirdi. Program öncesi sonrası değerlendirmeler karşılaştırıldığında VAS, SF-12 Fiziksel ve Mental skorları, 30 STS, TUG ve OBAEA için istatistiksel olarak anlamlı fark bulundu (p<0,01). Sonuç: Çalışmanın sonunda hibrit telerehabilitasyon programının LDH tanılı bireylerde ağrı, kas kuvveti, fonksiyonellik ve yaşam kalitesi üzerinde etkili olduğunu bulundu.

Introduction: Lumbar disc herniation (LDH) is a musculoskeletal problem that causes pain and sensory loss, and is characterized by loss of muscle strength, loss of function and decreased quality of life. The aim of this study is to investigate the effectiveness of the hybrid telerehabilitation program in individuals diagnosed with LDH. Material-Method: This study was carried out between January and June 2022 at Marmara University, Department of Physiotherapy and Rehabilitation. 51 individuals diagnosed with LDH who met the inclusion criteria and voluntarily participated in the study were included. Pain status of individuals was assessed with the Visual Analogue Scale (VAS); kinesiophobia status was evaluated with Tampa Scale for Kinesiophobia (TSK), quality of life was assessed with the 12-Item Short Form Health Survey (SF-12); lower extremity strength was evaluated with the 30 Second Sit to Stand Test (30 STS) and functionality was assessed with the Timed Up and Go Test (TUG) and the Oswestry Low Back Pain Disability Questionnaire (OLBPDQ). Individuals were included in an 8-week hybrid telerehabilitation program. Evaluations were made four times (D0: pre-program, D1: end of week 4, D2: end of week 8, D3: end of week 16) and changes were compared. Results: Of the 51 patients included in the program, 44 were female and 7 were male (mean age: 47.13±11.73 years). 22 patients were actively working. 5 patients had previously participated in a physical therapy and 134 rehabilitation program due to LDH, and 16 reported regularly engaging in physical activity. When the evaluations before and after the program were compared, a statistically significant difference was found for VAS, SF-12 Physical and Mental scores, 30 STS, TUG and OLBPDQ (p<0.01). Conclusion: At the end of the study, it was found that the hybrid telerehabilitation program was effective on pain, muscle strength, functionality and quality of life in individuals with LDH.
Lumbal di̇sk herni̇li̇ bi̇reylerde hi̇bri̇t telerehabi̇li̇tasyon programinin etki̇si̇
Keywords: Ağrı; Fonksiyonellik; Hibrit telerehabilitasyon; Lumbal disk hernisi; Kinezyofobi; Pain; Functionality; Hybrid telerehabilitation; Lumbal disc herniation; Kinesiophobia